The Bolsheviks in Russian society : the revolution and the civil wars - Brovkin, Vladimir N. (Yale University Press, 1997)
In this book distinguished scholars from East and West draw on recently opened archives to challenge the commonly held view that the Bolsheviks enjoyed widespread support and that their early history was simply a march toward inevitable victory. They show instead that during this period Russian society was at war with itself and with the Bolsheviks. Authors discuss such previously neglected subjects as government policies toward women and toward religious institutions, the protests of workers and peasants, and the anti-Bolshevik movements and parties. Describing not one civil war but several social, political, and military confrontations going on simultaneously, they portray a Russia in turmoil and on outcome that was by no means inevitable.